The Effect of Location, Product Innovation, and Service Quality on Consumer Satisfaction (A Case Study on Café Maballo) - Mey Enggane Limbongan; Novita Rante Paranduk (Universitas Kristen Indonesia Toraja, 2022)
This study focuses on location, product innovation, and service quality affecting consumer satisfaction. In addition, the investigated question is “Do location, product innovation, and service quality have an influence on customer satisfaction at Café Maballo?” Furthermore, the objective of this study was to find out to what extent the effect of location, innovation, and service quality on consumer satisfaction at Café Maballo. The employed data collection method was a questionnaire. The collected data were then analyzed using a validity test, reliability test, normality test, hypothesis testing, multiple regression analysis, t-test, F test, and coefficient of determination (R2). To facilitate the data processing, researchers used SPSS v. 25. The results of the t-test examining the effect of location on customer satisfaction showed that t_count was > t_table (0.734 > 1.66792) with a significant level below 0.1 (i.e., 0.000). Thus, the location does not have a significant effect on customer satisfaction at Café Maballo. Furthermore, H_O is accepted, meaning that the location does not partially affect customer satisfaction. In addition, the results of the t-test examining the effect of innovation on customer satisfaction presented that t_count was > t_table (3.253 < 1.66792), indicating that innovation has a positive and significant influence on customer satisfaction at Café Maballo. Additionally, the results of the t-test examining the effect of service quality on satisfaction revealed that t_count was > t_table (3.455 > 1.66792). Therefore, H_a is accepted, meaning that service quality affects consumer satisfaction at Café Maballo. Apart from that, the results of the F test showed that F_count was > F_table (19.203 > 3.13), indicating that location, innovation, and service quality simultaneously influence customer satisfaction at Café Maballo. Furthermore, the coefficient of determination presented an R-squared of 0.462 or 46%. This shows that the percentage of the influence of the independent variables on the dependent variable is 46% while the remaining 54% is from the influence of other variables not observed in this study.